Lichen records from La Rioja, Spain - Yavuz, Mustafa; Çobanoglu, Gülsah (Lazaroa, 2009)
As a by-product of the E.U. Socrates Comenius Project Meeting held in Alfaro, La Rioja Spain in 2006; a list of 35 lichen taxa collected in the region is presented. Nine species are new records for the Comunidad Autónoma de La Rioja: Buellia aethalea, Caloplaca crenularia, Caloplaca luteoalba, Candelariella aurella, Cladonia strepsilis, Lecanora dispersa, Lecanora piniperda, Lecanora saligna and Xanthoria polycarpa. Information on the localities and substrata of the collections made are provided.